Republic of Poland : Review Under the Flexible Credit Line Arrangement-Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Republic of Poland. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This paper discusses key findings of the Review Under the Flexible Credit Line (FCL) Arrangement for Poland. The authorities have taken measures to mitigate the economic slowdown and maintain macroeconomic stability. With subdued inflation, monetary policy has been accommodative during the first half of 2009. Measures have also been taken to safeguard financial stability. The IMF staff's assessment is that Poland continues to meet the qualification criteria for access to FCL resources and remains committed to responding appropriately to actual or potential balance of payments pressures.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet